The Most Frequently Recommended Urological Pelvic Floor Physiotherapy Techniques for Men Based on the Latest Scientific Research - Gałuszka, Aleksandra; Gałuszka, Maja; Różycka, Karolina; Mulawa, Magdalena; Mazur, Karolina; Piaszczyńska, Emilia; Matacz, Dominika; Drabik, Sandra; Krycia, Kamila; Adamczyk, Adrianna (Journal of Education, Health and Sport, 2026)
Urological dysfunctions, such as post-prostatectomy urinary incontinence, chronic pelvic pain syndrome and overactive bladder, constitute a significant clinical problem in men. Pelvic floor muscle physiotherapy is currently the most recommended conservative and supportive treatment option. The aim of this study was to analyze the latest scientific reports on the effectiveness of the most commonly used urological physiotherapy techniques for the pelvic floor in men. Material and methods consisted of a literature review conducted in databases such as PubMed, Scopus, and Web of Science. Publications were published between 2018 and 2025. Only randomized controlled trials, meta-analyses, and guidelines from scientific societies were included in the analysis: American Urological Association, International Continence Society, European Association of Urology, Polish Urological Association, Polish Continence Society, Polish Physiotherapy Society, and Polish Urogynecological Society. Results: The most effective techniques include pelvic floor muscle training (PFMT) supported by EMG biofeedback and electrostimulation. Additional effectiveness has been demonstrated with ultrasound therapy and other physical treatments. Multimodal therapy combining pelvic floor training, breathing exercises, and core stabilization accelerates the recovery of sphincter function after prostatectomy. The study’s conclusions indicate that urological physiotherapy based on pelvic floor muscle training with biofeedback and supported by electrostimulation and neuromodulation techniques may be the best standard of treatment for functional urological disorders in men. Individualized therapy and early initiation increase its effectiveness.